Acquired lymphangioma circumscriptum on the abdomen during pregnancy: A case report - Heidi Oi-Yee Li; Linda Mardiros; Jennifer Lipson (SAGE Open Medical Case Reports)
To our knowledge, acquired lymphangioma circumscriptum during pregnancy has only been reported on the vulva, and herein, we report a novel case of acquired lymphangioma circumscriptum during pregnancy on the abdomen. A 34-year-old woman presented with numerous papules draining clear fluid on her lower abdomen during the third trimester of her third pregnancy. She is healthy with no past medical history. Physical examination showed numerous clustered groups of hypopigmented flat-topped papules on the lower abdomen below the umbilicus. A punch biopsy showed epidermal acanthosis and hyperkeratosis and dilated lymphatic vessels in the superficial and upper dermis. Further imaging revealed no deeper lymphatic involvement and no underlying abdominal pathology. The favoured diagnosis was an acquired variant of lymphangioma circumscriptum on the abdomen, likely secondary to pregnancy. As the lesions were asymptomatic, no treatment was required. Dermatologists should recognize and differentiate this rare manifestation of acquired lymphangioma circumscriptum in pregnancy from other dermatoses.